(untitled) (World Economics and Finance Bulletin, 2023)
The analysis of functions of belonging and the assessment of the state of the control object are crucial processes in various fields, ranging from engineering and technology to social sciences and management. This article aims to delve into the significance and intricacies of these functions, exploring their impact on the overall performance and effectiveness of control systems. In today’s dynamic and complex world, control systems play a pivotal role in ensuring efficient operations, mitigating risks, and achieving desired outcomes. The functions of belonging and the assessment of the state of the control object provide valuable insights into the relationships and interactions between different components within a control system. By understanding these functions, researchers, practitioners, and decision-makers can enhance the design, implementation, and optimization of control systems across diverse domains. Through this exploration, we hope to stimulate further research, collaboration, and innovation in the field of control systems, fostering advancements that can drive progress in various industries and domains. By gaining a deeper understanding of these functions, we can unlock new possibilities for designing and managing robust and resilient control systems that are capable of meeting the challenges of our rapidly evolving world